The Application of Radical Marketing Strategies To Customer Behaviour Intention In Increasing Sales of Batik Jati Asih Products of The Umkm Unit Bumdes Kujati Perdana In Karangjati Village Pandaan Pasuruan - Muhammad Luthfi Alif Utama; Sudarmiatin Sudarmiatin (Dinasti International Journal of Education Management And Social Science, 2024)
The purpose of this study is to analyse the application of Radical Marketing strategies to Customer Behaviour Intention in increasing sales of Batik Jati Asih products of the UMKM unit of Bumdes Kujati Perdana in Karangjati Village Pandaan Pasuruan. Radical Marketing is an unusual marketing strategy used in influencing Customer Behaviour Intention to increase sales of Batik Jati Asih. This research uses a qualitative method with a phenomenological approach whose research data is obtained using techniques through interviews. The sample in this study were 10 Subject Informants consisting of the chairman of Batik Jati Asih, 4 Batik Craftsmen and 5 Jati Asih batik consumers who were selected using purposive sampling method. From the results of the Interview that the Batik Jati Asih Party can be obtained the results of the research that Batik Jati asih has implemented a Radical Marketing Strategy in influencing Customer Behaviour Intention which makes consumer perceptions can be fulfilled in their perceptions so as to cause purchases and repurchases. This is a positive impact in increasing sales of Batik Jati Asih products. So the Radical Marketing Strategy affects Customer Behaviour Intention in increasing sales of Jati Asih batik products.